Kedudukan Harta Bersama dalam Perkawinan Campuran Antara Warga Negara Indonesia dan Warga Negara Asing - Annisa Pebrina Harahap; Hening Hapsari Setyorini (LPPM Universitas Ekasakti Padang, 2023)
Marriage is a form of cooperation between a man and a woman in society under special regulations and this is taken into account by religion, state, and custom. In general, marriage is a process of uniting two different individuals into a husband and wife with the aim of building a household and strengthening brotherhood between families. Marriage not only concerns the individual of husband and wife but also concerns all family and community matters. The definition of marriage based on the provisions of Article 1 of Law Number 1 of 1974 concerning Marriage states that